Women illustrators on Instagram: digital influencers more committed to gender equality in social networks - Martín García, María Teresa; Martínez Solana, María Yolanda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
In recent years a new digital phenomenon has emerged, as a result of the development of social networks: the influencers. It is a trend closely related to the field of women's fashion and that increases sexist stereotypes. At the same time, a feminist current has become strong, led by millennial women (in many cases artists) who want to make real women visible and who take advantage of their influence on Instagram to claim gender equality. This paper analyzes the work and the main contributions of the most influential feminist instagramers, in contrast to fashion instagramers.